2020
DOI: 10.47540/ijsei.v1i2.59
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Leadership Strategies and Work Commitments in Maintaining Employee Performance in CV. Silvana Print & Advertising Kendari City Southeast Sulawesi

Abstract: The purpose of this study was to determine the description of the application of leadership strategies and work commitments of CV. Silvana Print & Advertising in maintaining employee performance. Data collection methods used was observation, open interview, and documentation. Analysis of the data in this research is a qualitative descriptive analysis through case studies. Based on the results of the study note that the leadership strategy and work commitment in maintaining employee performance on the CV. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…(Saks, 2006) found that there was a positive influence on employee engagement on employee performance. This research in 2019 was carried out again by reviewing the modeling carried out in 2006 by Saks with the results that it was proven that employee engagement had an effect on employee performance (Saks, 2019;Masri, 2020). (Dajani, 2015) in a study in Egypt found that employee engagement has a significant and positive effect on employee performance.…”
Section: Introductionmentioning
confidence: 99%
“…(Saks, 2006) found that there was a positive influence on employee engagement on employee performance. This research in 2019 was carried out again by reviewing the modeling carried out in 2006 by Saks with the results that it was proven that employee engagement had an effect on employee performance (Saks, 2019;Masri, 2020). (Dajani, 2015) in a study in Egypt found that employee engagement has a significant and positive effect on employee performance.…”
Section: Introductionmentioning
confidence: 99%